2018
DOI: 10.1039/c8ta01800f
|View full text |Cite
|
Sign up to set email alerts
|

Designing solution chemistries for the low-temperature synthesis of sulfide-based solid electrolytes

Abstract: A new solution-based synthesis method to produce a high quality Li2S–P2S5 solid electrolyte was developed by using a strong nucleophile of LiC2H5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 25 publications
1
59
1
Order By: Relevance
“…More recently, elaborate liquid‐phase syntheses of sulfide SEs have been reported. High‐purity β‐Li 3 PS 4 (0.13 mS cm −1 ) was prepared by adding LiSC 2 H 5 as a nucleophilic agent during the liquid‐phase synthesis because the THF‐soluble intermediate species of P 2 S 5 ‐LiSC 2 H 5 stimulates the reactivity . Adding excess sulfur for the liquid‐phase synthesis of Li 3 PS 4 allowed the conversion of the suspension into a homogeneous solution although the as‐obtained SE materials showed poor conductivities of <10 −5 S cm −1 .…”
Section: Figurementioning
confidence: 99%
“…More recently, elaborate liquid‐phase syntheses of sulfide SEs have been reported. High‐purity β‐Li 3 PS 4 (0.13 mS cm −1 ) was prepared by adding LiSC 2 H 5 as a nucleophilic agent during the liquid‐phase synthesis because the THF‐soluble intermediate species of P 2 S 5 ‐LiSC 2 H 5 stimulates the reactivity . Adding excess sulfur for the liquid‐phase synthesis of Li 3 PS 4 allowed the conversion of the suspension into a homogeneous solution although the as‐obtained SE materials showed poor conductivities of <10 −5 S cm −1 .…”
Section: Figurementioning
confidence: 99%
“… 17 , 34 42 Several studies reported that the Li 2 S–P 2 S 5 solid electrolyte was synthesized via stirring Li 2 S and P 2 S 5 in polar organic solvents. 17 , 34 , 38 − 41 In all cases, the ionic conductivity of Li 3 PS 4 prepared via liquid-phase synthesis was lower than that via solid-phase synthesis. 17 , 34 , 38 − 41 The relatively low ionic conductivity of Li 3 PS 4 in the liquid phase is hypothesized to be due to two factors: the residual unreacted Li 2 S and/or its relatively high crystallinity.…”
Section: Introductionmentioning
confidence: 96%
“… 17 , 34 , 38 − 41 In all cases, the ionic conductivity of Li 3 PS 4 prepared via liquid-phase synthesis was lower than that via solid-phase synthesis. 17 , 34 , 38 − 41 The relatively low ionic conductivity of Li 3 PS 4 in the liquid phase is hypothesized to be due to two factors: the residual unreacted Li 2 S and/or its relatively high crystallinity. 39 , 43 , 44 Shin et al reported that the reason for the low ionic conductivity was the unreacted starting material, Li 2 S. 39 However, the unreacted Li 2 S was not confirmed using X-ray diffraction (XRD) and/or Raman spectroscopy in other studies.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations